(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Yemelova A. P. The role of zemstvos in the development of labor training in Katerynoslav province (end of XIX - beginning of XX century). The article examines the activities of zemstvo Ekaterinoslav province in the sectors of education and the development of labor training.